Importance of mother tongue science in primary grades - YULDASHEVA AZIZAKHAN (CONFERENCE OF NATURAL AND APPLIED SCIENCES IN SCIENTIFIC INNOVATIVE RESEARCH, 2024)
the article talks about the importance, necessity, purpose and tasks of mother tongue science in 1-2 grades and its connection with other subjects and the essence of teaching